The Role of Family Law in Confronting Polygamy Practices in Contemporary Society - Abdulah Pakarti, Muhammad Husni; Utama, Sofyan Mei; Farid, Diana; Mabruri, Kemal Al Kautsar; Fathiah, Iffah (Syakhsiyah Jurnal Hukum Keluarga Islam, 2023)
Polygamy is a marital practice in which a man simultaneously has more than one wife. In contemporary society, this practice often poses various legal and social challenges. This study aims to analyze the role of family law in regulating polygamy, protecting individual rights, and maintaining a balance between religious freedom and women's rights. Family law plays a central role in ensuring that polygamy is conducted with the principles of justice, equality, and protection of the wives' rights. This research uses a qualitative method with a literature study approach. In contrast, this research's primary and secondary sources are journals published with national and international reputation indexes, as well as books, laws, and so on that support this research. Data analysis uses description analysis, data following the actual, and then the data is compiled, processed, and analyzed to provide an overview of the existing problems. The results show that polygamy remains a controversial issue in contemporary society. Family law is essential in regulating and dealing with this practice, significantly impacting individuals, families, and communities. This research provides a further understanding of the complexity of the role of family law in the context of polygamy. It can serve as a basis for further discussion on regulating and protecting individual rights in a changing society.